TRADISI SIMA’AN DALAM PENGUATAN HAFALAN AL-QUR’AN DI PONDOK PESANTREN - Ahmad Mu’is; Rohit Kurniawan; Dewi Pratiwi; Hendri Handiyan (Amsal Al-Qur’an: Jurnal Al-Qur’an dan Hadis, 2025)
. This study is entitled The Tradition of Sima’an in Strengthening Qur’anic Memorization at Mustafawiyah Islamic Boarding School, Purba Baru. The purpose of this research is to describe in depth the implementation of the sima’an tradition and analyze its role in strengthening the memorization of the Qur’an among students (santri). This research uses a descriptive qualitative approach with data collection techniques including observation, in-depth interviews, and documentation. The research subjects consist of Qur’an memorizing students, supervising teachers (ustaz), and pesantren administrators.The results of the study show that the sima’an tradition at Mustafawiyah Purba Baru Islamic Boarding School is a regular activity conducted in the form of group Qur’anic recitation listening, where students take turns reciting from memory in front of peers or teachers. This activity serves not only as a means of evaluating memorization progress but also as a tool for improving recitation accuracy, increasing focus and attention, training mental resilience, and strengthening memory retention of the Qur’anic verses. This tradition has been maintained for generations and has become a cultural heritage of the pesantren. Supporting factors for the success of sima’an include student discipline, exemplary teachers, strong institutional support, and the internal motivation of students to become hafiz or hafizah. However, there are also challenges such as feelings of boredom, time management issues, and concentration disturbances that students must overcome. The conclusion of this study indicates that the sima’an tradition plays a significant role in strengthening Qur’anic memorization and needs to be preserved and developed further in the future.